Scapula Fractures in Elite Soccer and Rugby Players. Issue 12 (27th November 2019) - McIntosh, Jerome; Akhbari, Pouya; Malhas, Amar; Funk, Lennard
Background: Scapula fractures are uncommon in sports and are poorly understood in this patient group. Purpose: To report on scapula fractures in contact and collision athletes and assess the injury patterns of different mechanisms of injury. Study Design: Case series; Level of evidence, 4. Methods: A retrospective case series was performed of all sports-related scapula fractures treated at a single institution between 2007 and 2015. The mechanisms of injury were divided into direct lateral impact, fall onto an outstretched arm, or abduction/external rotation. Results: A total of 11 patients were identified: 9 professional rugby players, 1 professional soccer player, and 1 amateur soccer player. The mean age was 28 years (range, 18-35 years). The mean return to play was 127 days in those treated nonoperatively and 163 days in those treated operatively. A direct impact mechanism occurred in 7 patients, all of whom sustained glenoid neck and body fractures and were treated nonoperatively. Two rugby players had a concomitant suprascapular nerve injury. An outstretched arm mechanism occurred in 2 cases, leading to posterior and inferior glenoid fractures. Both patients were treated operatively. An abduction/external rotation mechanism occurred in 2 cases, resulting in an anteroinferior and an anterior glenoid rim fracture. One case was treated operatively and the other was treated nonoperatively. Of those with glenoid fractures, 75% were not visible on plain radiographs and required further imaging. Conclusion: Scapula fractures acquired in sports are a serious injury with a prolonged recovery period. The mechanism of injury can help predict the injury pattern and highlight the need for further imaging. There is a high association with suprascapular nerve injuries.